2021
DOI: 10.1002/hec.4448
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance and subjective well‐being: Evidence from two healthcare reforms in the United States

Abstract: Health insurance plays a major role in mitigating the financial losses of households due to unexpected sickness. However, health insurance coverage is generally suboptimal due to market failures such as information asymmetry. To alleviate this under-insurance problem, many governments have attempted to expand health insurance coverage. Due to the financial burden of expanding health insurance coverage, it is of great interest to both researchers and policymakers to understand the welfare impacts of gaining acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 74 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…The association between health insurance and SWB (e.g. happiness, life satisfaction) has been of long-standing interest to researchers and policymakers seeking to understand the broader welfare impacts of gaining health insurance coverage ( Kim and Koh, 2022 ).…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…The association between health insurance and SWB (e.g. happiness, life satisfaction) has been of long-standing interest to researchers and policymakers seeking to understand the broader welfare impacts of gaining health insurance coverage ( Kim and Koh, 2022 ).…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…Internal factors refer to their own physiological conditions and self-awareness, etc., which may affect the formation of individuals' behavioral habits, mainly including gender [22,23], personality [24,25], health [26,27], religious beliefs [28,29], and values [30,31]. In addition to these, factors such as educational status [32,33] and insurance [34,35] also have a significant impact on residents' happiness.…”
Section: Subjective Happiness Researchmentioning
confidence: 99%
“…Wu and Li found that health insurance could help older people feel secure and was positively associated with their physical and mental health (41). Kim and Koh found that lack of health insurance had a negative impact on the subjective wellbeing of the general population after controlling for individual self-assessed health status and other socioeconomic factors (42). While the aim of universal health coverage is to ensure equal access to health services, Liao et al found that universal health coverage also improved subjective wellbeing among older people, particularly older women (43).…”
Section: Literature Review Factors Influencing the Life Satisfaction ...mentioning
confidence: 99%